A construção de mundos na literatura não-realista - Julio Cesar Jeha (1991)
This dissertation follows a semiotic line in the study of modeling systems in non-realist literature. The first part deals with the action of the sign in nature and in the specifically human sphere. To the sign it is indifferent whether the object to which it refers exists in nature or only in the cognition of the experiencing organism. This characteristic of the sign enables animals to deceive and be deceived and, later, it enables humans to imagine and create beings without physical correlatives. Also from this characteristic arise language and all postlinguistic institutions. In other words, this possibility of the action of the sign gives birth to culture, by which the human being transcends the barriers of a biological heritage and the limits of the physical world. The second part analyses what this indifference in signification implies to literature, mainly to the theory of mimesis. On the one hand, cognition always occurs through comparison or contrast: the absolutely new is not cognizable. On the other, the human being distinguishes himself from other animals as he becomes able to disconnect relations from their bases and fundaments and reconnect them to other bases or fundaments. The action of the sign always contains some mimetic element, as it repeats an object or an interpretant, and some poietic element, as it brings about something that did not exist in experience. In literary creation (as in any creation) poiesisthe capacity specific to human beings of playing with relationspredominates. This enables us to define fantasy in literature as an intentional tlivorgence from a reality defined by consensus. The third part focuses on the models or modeling systems which model experience and the creation of new worlds, whetlier they come into existence physically or only as possibilities. Within these modeling systems, languageas deviated to communication appears as the origin of all the others, be they forms of government, religious beliefs, or scientific and philosophical theories about being and its ways of cognition and existence. Here texts from widely different sources are compared without any preoccupation with genres, periods or critical fortiine, in a comparative analysis of the working of the four main modeling systemsperception, language, religion, and sciencein the creation of possible and impossible worlds. The conclusion is that the mimesis in fantastic literature is one of interpretant and not one of object, as in the figurative and specular mimesis of realist literature.